HUBUNGAN INDEKS MASSA TUBUH DENGAN KADAR KOLESTEROL PADA LANSIA DI WILAYAH KERJA PUSKESMAS KOTA BATAM - Erda, Roza; Yunaspi , Didi; Nuraisyah , Siti; Devi Putri , Yulia (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
High cholesterol levels (hypercholesterolemia) is a very serious problem because it is one of the most important risk factors for heart disease and hypertension. Abnormalities found in increasing total cholesterol levels. The purpose of this study was to assess the relationship between body mass index and cholesterol levels in the elderly at Health Center, Batam City. This study used Observational Analitic method of cross-sectional approach. The ampling technique used simple random sampling of 65 respondents. This research was conducted in the work area of the Health Center, Batam City in 2022. the tools used to measure Body Mass Index (BMI) with digital scales with an accuracy of 0.1 kg. measuring height is a stature meter with a length range of 0-200 cm, measuring cholesterol levels with Cholesterol Meter. Univariate analysis in this study consists of independent variables, namely BMI (body mass index) and the dependent variable, namely Total Cholesterol Levels in the elderly, while bivariate analysis uses the chi-square test (x²). There is a significant relationship between the relationship between body mass index and cholesterol levels in the elderly in the Health Center Working Area, Batam City in 2022, with the results; statistical tests obtained a p-value of 0.000 (p-value <0.05). For Health Services It is expected to provide counseling to the elderly to better assist and help to realize health